Transmedia Lieracy: Double Traction Mechanism - Medina Téllez Girón, Andrea (Tropelías: Review of Literary Theory and Comparative Literature, 2019)
This proposal is framed in Lotman’s concept of semiosphere, in this sense transmedia literacy is considered as a connection of meaning-making bridges through different texts, texts are semiotic spaces. The connection across texts is made by the similarity instead of the plurality of texts, media, context, modalities, etc. This connection takes place thanks to textuality, that is an inherent text quality and is the basis of transmedia literacy, textuality allows the flow in the middle of diversity. Textuality lies on the concept of the hyperlink, intermediality and transmedia. The hyperlink is basic for the textual architecture, whether is a spreadable text in media or monomedial and, the interactivity with the reader. Hyperlinks, manifest or potential, establish intermedial relationships for the modes of representation. At the same time, intermediality builts a transmedia context, which can be of two types: narrow to one medium that forms a transmedia text or, extended to different media, that forms a transtext.